Population Structure and Pathotype Diversity of the Wheat Blast Pathogen Magnaporthe oryzae 25 Years After Its Emergence in Brazil - Nunes Maciel, Joao L.; Ceresini, Paulo C. [UNESP]; Castroagudin, Vanina L. [UNESP]; Zala, Marcelo; Kema, Gerrit H. J.; McDonald, Bruce A. (Amer Phytopathological Soc, 2014)
Since its first report in Brazil in 1985, wheat blast, caused by Magnaporthe oryzae (anamorph: Pyricularia oryzae), has become increasingly important in South America, where the disease is still spreading. We used 11 microsatellite loci to elucidate the population structure of the wheat blast pathogen in wheat fields in central-western, southeastern, and southern Brazil. No subdivision was found among the wheat-infecting populations, consistent with high levels of gene flow across a large spatial scale. Although the clonal fraction was relatively high and the two mating type idiomorphs (MAT1-1 and MAT1-2) were not at similar frequencies, the clone-corrected populations from Distrito Federal and Goias, Minas Triangle, and Sao Paulo were in gametic equilibrium. Based on these findings, we propose that populations of the wheat blast pathogen exhibit a mixed reproductive system in which sexual reproduction is followed by the local dispersal of clones. Seedling virulence assays with local wheat cultivars differentiated 14 pathotypes in the current population. Detached head virulence assays differentiated eight virulence groups on the same wheat cultivars. There was no correlation between seedling and head reactions.